Acrobats - The Story of the Urban Spaceman - Karrento, Johan (Sweden, 2005)
Supported by OSI-Budapest Arts and Culture Program. Duration: 00:40:21 The images of the film are of young people from middle-class European societies: wealthy, surrounded with all they need. These stereotypical images of the consumer society are co-presented with a sound track composed of interviews with Africans living in Europe, who express their opinions and experiences about the European life style and European values.